2022
DOI: 10.3389/fcvm.2022.926064
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cardiovascular aging following allogeneic hematopoietic cell transplantation for hematological malignancy

Abstract: IntroductionAllogeneic hematopoietic cell transplantation (allo-HCT) offers a potential cure for high-risk hematological malignancy; however, long-term survivors experience increased cardiovascular morbidity and mortality. It is unclear how allo-HCT impacts cardiovascular function in the short-term. Thus, this 3-month prospective study sought to evaluate the short-term cardiovascular impact of allo-HCT in hematological cancer patients, compared to an age-matched non-cancer control group.MethodsBefore and ~3-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
3
4
0
Order By: Relevance
“…Therefore, with the 7.8 ml kg −1 min −1 deficit in O 2peak observed among the survivors in our study it is not unexpected that this population are burdened by markedly elevated rates of overt CVD, and premature cardiovascular and all-cause mortality. Our results are consistent with Armenian et al 21 who found O 2peak to be 22% below predicted values at a median of 9.8 years post-SCT, but intriguingly, are in contrast to the degree of O 2 peak impairment observed among short, and very long-term survivors 13 , 22 . Indeed, O 2peak has been shown to be 49% below predicted among early survivors (~ 3 months post-SCT) 13 and 11% below predicted among very long-term survivors of allo-SCT (median 17 years [range 6–26] post-SCT) 22 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, with the 7.8 ml kg −1 min −1 deficit in O 2peak observed among the survivors in our study it is not unexpected that this population are burdened by markedly elevated rates of overt CVD, and premature cardiovascular and all-cause mortality. Our results are consistent with Armenian et al 21 who found O 2peak to be 22% below predicted values at a median of 9.8 years post-SCT, but intriguingly, are in contrast to the degree of O 2 peak impairment observed among short, and very long-term survivors 13 , 22 . Indeed, O 2peak has been shown to be 49% below predicted among early survivors (~ 3 months post-SCT) 13 and 11% below predicted among very long-term survivors of allo-SCT (median 17 years [range 6–26] post-SCT) 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with Armenian et al 21 who found O 2peak to be 22% below predicted values at a median of 9.8 years post-SCT, but intriguingly, are in contrast to the degree of O 2 peak impairment observed among short, and very long-term survivors 13 , 22 . Indeed, O 2peak has been shown to be 49% below predicted among early survivors (~ 3 months post-SCT) 13 and 11% below predicted among very long-term survivors of allo-SCT (median 17 years [range 6–26] post-SCT) 22 . It may therefore be reasonable to speculate that allo-SCT-induced impairments in O 2peak ‘recover’ to some degree over time.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations